Proposed Managements of 137Cs Contaminated Soil: Case Study in South Tangerang City - B. Setiawan; D. Iskandar; G. Nurliati; H. Sriwahyuni; M Mirawaty; P. A. Artiani; K. Heriyanto; N. E. Ekaningrum; Y. Purwanto; S Sumarbagiono (PPIKSN-BATAN, 2021)
Recently, BAPETEN found contamination of 137Cs while testing environmental radiation monitoring equipment in an area in South Tangerang City. The area, therefore, needs to be cleaned up by performing decontamination followed by the activity of treating the contaminated soil. The decontamination works were carried out by excavating the contaminated soil on the surface to a depth of more than 1.5 m, and then the soils were put into the 100L drum. Decontamination work resulted in a significant reduction dose exposure in the area to 0.3-0.75 mSv/h. The drums containing contaminated soil were then sent to the interim storage facility in BATAN Serpong facility for further treatment. To resolve the 137Cs contaminant, some alternatives in the decontamination and management of the contaminated soils were studied. Some techniques and strategies for decontamination and managing 137Cs are presented in this paper. Management that involves wet and dry methods will be proposed in this paper. By comparing and evaluating various alternative management methods, an appropriate method for treating the contaminated soil in South Tangerang City can be obtained. The objective of the study was to find a suitable management method for the contaminated soil based on the proposed alternative management methods.In the present case, the compaction method seems promising for use soon.